Efficiency divergence and convergence in China’s hospital sector: empirical insights from Guangdong Province using a multi-method approach - Yu, Jianxin; Xu, Yongyi; Wu, Jindong; Wu, Baoling; Zhang, Zijuan; Huang, Weizhang; Gong, Hanxiang (Frontiers in Public Health, 2025)
BackgroundSince the launch of China’s new round of healthcare system reforms in 2009, improving service efficiency has become a critical focus for enhancing the equitable allocation of medical resources and overall healthcare quality. Guangdong Province, as one of China’s most economically dynamic regions, faces significant challenges in addressing disparities in hospital service efficiency and optimizing resource utilization.ObjectiveThis study aims to comprehensively analyze the differences, dynamic evolution, and influencing factors of service efficiency among healthcare institutions in Guangdong Province. The goal is to provide scientific evidence for narrowing efficiency gaps between hospitals, enhancing overall service quality, and informing policy development.MethodsA comprehensive evaluation system for hospital service efficiency in Guangdong Province was constructed. Data Envelopment Analysis (DEA) was employed to measure efficiency levels. The Dagum Gini coefficient decomposition method was used to examine the sources of efficiency disparities among different hospital categories. Kernel density estimation was employed to investigate the dynamic distribution of service quality, while the Tobit regression model was used to identify key factors influencing healthcare service efficiency.ResultsThe findings indicate that significant differences in service efficiency existed among various categories of hospitals in Guangdong Province from 2018 to 2022. Specialty hospitals demonstrated the highest average overall efficiency, whereas general hospitals recorded the lowest efficiency and growth rates. The performance of healthcare institutions in terms of pure technical efficiency, scale efficiency, and overall efficiency showed fluctuations, but a general trend of recovery was observed. The Dagum Gini coefficient decomposition revealed a relatively high degree of internal efficiency inequality within general hospitals, peaking in 2021, reflecting heterogeneity in scale, management, and resource allocation. The Gini coefficient between specialty and general hospitals was also comparatively high. Kernel density estimation indicated a bimodal distribution in service efficiency, highlighting the heterogeneity of efficiency levels and an increase in hospital categories with lower service quality. The Tobit model analysis confirmed that a lower mortality rate among low-risk cases had a significant positive impact on service efficiency, while average appointment rate, the proportion of health technicians, and the proportion of senior health technicians had significant negative effects.ConclusionIt is recommended to deepen reforms of internal governance structures and enhance cross-level collaboration within healthcare institutions. Establishing efficiency-oriented mechanisms, optimizing human resource management, strengthening departmental collaboration, and leveraging information technology can effectively improve the service efficiency of healthcare institutions in Guangdong Province.